2019
DOI: 10.26456/pcascnn/2019.11.298
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SYNTHESIS PARAMETERS ON DIMENSIONAL CHARACTERISTICS OF Fe3O4 NANOPARTICLES: NEURAL-NETWORK RESEARCH

Abstract: Рецензирование статей осуществляется на основании Положения о рецензировании статей и материалов для опубликования в Межвузовском сборнике научных трудов «Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов». Официальный сайт издания в сети Интернет: https://www.physchemaspects.ru Ф50 Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов [Текст].  Тверь: Твер. гос. ун-т, 2019.  Вып. 11.  680 с. Зарегистрирован Федеральной службой по надзору в сфере связи, информ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As a result of the experiment, the values of the response functions for each experiment were obtained (Table 6). As a result of mathematical processing of the obtained experimental data, a neural network was formed in Neural Statistica Network 12.0 software [33], the architecture of which is shown in Figure 1. As a result of the experiment, the values of the response functions for each experiment were obtained (Table 6).…”
Section: Determination Of the Optimal Complexing Agent For The Remova...mentioning
confidence: 99%
“…As a result of the experiment, the values of the response functions for each experiment were obtained (Table 6). As a result of mathematical processing of the obtained experimental data, a neural network was formed in Neural Statistica Network 12.0 software [33], the architecture of which is shown in Figure 1. As a result of the experiment, the values of the response functions for each experiment were obtained (Table 6).…”
Section: Determination Of the Optimal Complexing Agent For The Remova...mentioning
confidence: 99%
“…As a result of quantum chemical modeling, it was found that silver nanoparticles can interact with the following amino acids: Proline, glutamine, lysine, arginine, asparagine, histidine, glutamic and aspartic acids, tryptophan, and cysteine, which is due to the presence of additional -NH2, -NH, -SH and -COOH groups in these amino acids that are not involved in the formation of a peptide bond. These free additional groups make possible interaction with nanosilver [23,47]. Thus, the interaction of silver nanoparticles with threonine, serine, and tyrosine is unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…The most important of which is the essential trace element zinc. The most noteworthy is the highly biologically active colloidal hellate forms presented in the following works [1,[22][23][24][25]. It is also worth noting the development of digitalization of medical wards [3,26] of computer simulation of operations and the use of an electronic pharmacologist in postoperative therapy [2].…”
mentioning
confidence: 99%
“…The main ones are as follows: participation in the construction of tissues, maintenance of homeostasis of the internal environment of the body, ensuring the balance of cell membranes, activation of biochemical reactions through enzymatic systems, direct or indirect influence on the function of endocrine glands, impact on the symbiotic microflora of the gastrointestinal tract and others [1]. The main way of the effect of trace elements on the body is expressed by their inclusion in the composition of proteins, nucleic and amino acids, and biocatalysts, as well as participation in the maintenance of ion transport [2]. Trace elements after absorption in the intestine are transported by blood, deposited mainly in the liver, and are included in the composition of various enzymes, hormones, vitamins, and other biologically active substances [3][4][5].…”
Section: Introductionmentioning
confidence: 99%